The Effect Of Waterfront City Development On The Economic Welfare Of Coastal Communities (Study In Beting Village, East Pontianak District, Pontianak City) - Andi Setiawan; Ghina Firyaliani Zalfa (Jurnal Indonesia Sosial Teknologi, 2023)
This study aims to analyze the effect of waterfront city development on coastal economic development in Beting Village, East Pontianak District, Pontianak City. This is due to the low economy of the community so many of them are involved in buying and selling drugs which then damages the good image of Kampung Beting. Data from 100 respondents were analyzed using quantitative analysis methods with simple linear regression. The results showed that the waterfront city had a significant effect on the welfare of the coastal economy of the Betting Village community. This is because according to the conditions the waterfront itself is appropriate so that it can attract tourists to visit the area who come and then open opportunities for local people to open various types of businesses such as boat rentals, taverns or cafes, and selling souvenirs.